Establishment of Highly Transplantable Cholangiocarcinoma Cell Lines from a Patient-Derived Xenograft Mouse Model - Vaeteewoottacharn, Kulthida (Cells, 2019)
Cholangiocarcinoma (CCA) is a deadly malignant tumor of the liver. It is a significant health problem in Thailand. The critical obstacles of CCA diagnosis and treatment are the high heterogeneity of disease and considerable resistance to treatment. Recent multi-omics studies revealed the promising targets for CCA treatment; however, limited models for drug discovery are available. This study aimed to develop a patient-derived xenograft (PDX) model as well as PDX-derived cell lines of CCA for future drug screening. From a total of 16 CCA frozen tissues, 75% (eight intrahepatic and four extrahepatic subtypes) were successfully grown and subpassaged in Balb/c Rag-2(-/-)/Jak3(-/-) mice. A shorter duration of PDX growth was observed during F0 to F2 transplantation; concomitantly, increased Oct-3/4 and Sox2 were evidenced in 50% and 33%, respectively, of serial PDXs. Only four cell lines were established. The cell lines exhibited either bile duct (KKK-D049 and KKK-D068) or combined hepatobiliary origin (KKK-D131 and KKK-D138). These cell lines acquired high transplantation efficiency in both subcutaneous (100%) and intrasplenic (88%) transplantation models. The subcutaneously transplanted xenograft retained the histological architecture as in the patient tissues. Our models of CCA PDX and PDX-derived cell lines would be a useful platform for CCA precision medicine.